The Role of Spirituality in the Practice of Adult Education Leaders - Jeanette Justice Fleming; Bradley C. Courtenay (Adult Education Research Conference, 2006)
Leaders defined spirituality as different from, but related to religion, part of their identity, and as a connection to a Higher Being, to others, and to nature. Spirituality provided a calling to profession, instilled an ethical framework and served as a resource in times of challenge. It influenced use of power, decision making, and communication with coworkers. Participants exhibited a variety of leadership styles reflecting individual perceptions of spirituality.
Keywords: Spirituality; leadership; adult education